Transdermal Delivery of Azilsartan: Formulation Strategies and Performance Evaluation - A. Rekha Devi (Asian Journal of Pharmaceutics (AJP), 2024)
Aims: Matrix-type systems were developed in the present study by using various polymers including sodium carboxymethyl cellulose and eudragits with various concentrations. Materials and Methods: In the present work, an attempt has been made to develop a matrix-type transdermal therapeutic system comprising of Azilsartan with different concentrations of sodium carboxyl methyl cellulose and Eudragit using solvent evaporation technique. The physicochemical compatibility of the drug and the polymers was studied by infrared spectroscopy. Results and Discussion: The results obtained showed no physical-chemical incompatibility between the drug and the polymers. The in vitro drug diffusion studies from the formulation were found to be a sustained release effect. All the evaluation parameters obtained from the best formulation were found to be satisfactory. Conclusion: The data obtained from the in vitro release studies were fitted to various kinetic models; it was found that drug release follows the Peppas model release by diffusion technique from the polymer.